2009
DOI: 10.1007/s10597-009-9256-x
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Conceptualization of Adolescents’ Mental Health Problems: Who Adopts a Psychiatric Perspective and Does It Make a Difference?

Abstract: How parents give meaning to the problems of adolescents diagnosed with mental disorders and receiving treatment is likely related to important outcomes including parental well-being and commitment to treatment, as well as their own behaviors and reactions to their child. The aim of this cross-sectional, mixed-method study of 70 parents of adolescents receiving wraparound mental health services is to examine: (1) how parents conceptualize their child's MH problems; (2) factors related to parents' conceptualizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 39 publications
(54 reference statements)
6
26
0
2
Order By: Relevance
“…Parents in that study most frequently identified ADHD, followed by depression and oppositional defiant disorder, as the appropriate diagnosis (Teagle, 2002). In a mixed-methods study by Moses (2011) parents expressed significant feelings of uncertainty regarding their ability to recognize mental health disorders in their children. That ability appears to be crucial, as disorder recognition is strongly associated with accessing services (Teagle, 2002).…”
Section: Mental Health Literacy In Parents and Caregivers: Identificamentioning
confidence: 99%
“…Parents in that study most frequently identified ADHD, followed by depression and oppositional defiant disorder, as the appropriate diagnosis (Teagle, 2002). In a mixed-methods study by Moses (2011) parents expressed significant feelings of uncertainty regarding their ability to recognize mental health disorders in their children. That ability appears to be crucial, as disorder recognition is strongly associated with accessing services (Teagle, 2002).…”
Section: Mental Health Literacy In Parents and Caregivers: Identificamentioning
confidence: 99%
“…62 Minority parents may have a higher threshold for labeling symptoms as a problem that requires professional care, 67 a lower likelihood to medicalize problems, 60, 68 or alternative conceptualizations of children’s problems. 69 Low healthcare literacy may also hinder parents’ ability to register for public insurance and understand coverage benefits and treatment directives. 70 Research in this area unfortunately does not estimate the use of behavioral health services as a function of these perceptions.…”
Section: Potential Mechanisms Of Behavioral Health Service Disparitiesmentioning
confidence: 99%
“…Parents with the other conceptualizations (i.e., alternative or uncertain) “tended to view their child’s problems as reactions to life circumstances” (p.78), which was the key distinguishing feature of caregivers we categorized as having a response conceptualization. Further, Moses (2011) reported that parents’ with a psychiatric conceptualization reported significantly more sadness and pessimism (i.e., indications of caregiver strain in our study) than parents with other conceptualizations, and were significantly more likely to have sought counseling for their own needs (i.e., formal help-seeking). While the labels we choose to use are different from those identified by Moses (2011), consistencies in the main findings are remarkable.…”
Section: Discussionmentioning
confidence: 54%
“…Our coding process and analyses developed independently of a larger study reporting similar findings (Moses, 2011). Moses (2011) examined factors related to parents’ conceptualizations of their child’s mental health problems and differential responses using mixed methods and a larger sample, and reported that parents’ conceptualizations were either in-line with the psychiatric/medical labels (analogous to our stressful event conceptualization) or they reported alternative explanations or uncertainty about the cause of their children’s problems. Parents with the other conceptualizations (i.e., alternative or uncertain) “tended to view their child’s problems as reactions to life circumstances” (p.78), which was the key distinguishing feature of caregivers we categorized as having a response conceptualization.…”
Section: Discussionmentioning
confidence: 99%